Leisure Activities in the Outdoors Learning, Developing and Challenging - Baker, Mandi; Carr, Neil; Stewart, Emma J. (CABI, 2021)
The benefits of being outdoors in a leisure context are widely acknowledged across a range of disciplinary perspectives (including tourism, therapeutics, education and recreation). These benefits include the development of: health and wellbeing; social skills; leadership and facilitation skills; personal, emotional and reflective abilities; confidence and identity creation.Drawing on a variety of perspectives, geographies and approaches, this book explores the opportunities that leisure in the outdoors provides for learning, developing and challenging. The authors in this collection challenge dominant discourses of outdoor leisure through their selection of outdoor activities, theoretical approaches and modes of representation. All offer fresh insights and thinking into how leisure in the outdoors can be understood. The book covers a range of outdoor conceptualisations that challenge the reader to think deeply and broadly about the common threads which bind the broad field of outdoor leisure together. The experiences explored in this book range from suburban outdoors to wild places, surfing to mindful reflection, and trail walking to Nordic skiing, and encompass a broad spectrum of people.This book will appeal to outdoor scholars from a variety of contexts, including recreation, tourism, and adventure. It provides:·original and leading research across layers of meaning attributed to and drawn from leisure experiences in the outdoors;·value in theorising the notions of outdoor experiences;·a variety and scope of contexts and approaches for students to draw on when learning about the field of outdoor leisure.